Dampak Hukum Pengakuan Terhadap Palestina Menurut Hukum Internasional - Deli Waryenti (University Of Bengkulu Law Journal, 2025)
Palestine, a country that has received recognition from many nations, faces unique challenges in achieving equal standing with other countries. These challenges include the territory still under the control of Israel and Hamas, a population largely composed of Israeli citizens, and a government structure that is divided between two entities-Hamas and Fatah/PLO. Despite the explicit and de jure recognition from various countries, Palestine's inability to function as a subject of International Law in practice renders this recognition ineffective. On the other hand, Israel has experienced a significant impact from this recognition, notably in the form of damaged diplomatic relations with several countries.